Robotics for Natural Orifice Transluminal Endoscopic Surgery: A Review - Xiaona Wang; Max Q.-H. Meng (Journal of Robotics)
Natural Orifice Transluminal Endoscopic Surgery (NOTES) involves accessing the abdominal cavity via one of the bodies’ natural orifices, for example, mouth, anus, or vagina. This new surgical procedure is very appealing from patients’ perspectives because it eliminates completely abdominal wall aggression and promises to reduce postoperative pain, in addition to all other advantages brought by laparoscopic surgery. However, the constraints imposed by both the mode of access and the limited technology currently available make NOTES very challenging for the surgeons. Redesign of the instruments is imperative in order to make this emerging operative access safe and reproducible. In this paper, we survey on the state-of-the-art devices used in NOTES and introduce both the flexible instruments based on improvement of current endoscopic platforms and the revolutionary concept of robotic platforms based on the convergence of communication and micromechatronics technologies. The advantages and limitations of each category are addressed. Potential solutions are proposed to improve the existing designs and develop robust and stable robotic platforms for NOTES.